Defining Life Skills in health promotion at school: a scoping review - Darlington-Bernard, Adeline; Salque, Corélie; Masson, Julien; Darlington, Emily; Carvalho, Graça S.; Carrouel, Florence (Frontiers in Public Health, 2023)
Background: Life skills have been central to Health Promotion interventions and programmes with children and adolescents for over 40 years. School is a strategic setting for Life Skills education. Recently, policy-and decision-makers have focused on Like Skills development for youth. Research on Life Skills has gained momentum. Different terms are used to discuss and define Life Skills. Research identifies a lack of conceptual definition. The purpose of this study is to identify the definitions in the literature in English and French, and to reach a conceptual and consensual definition.Method: The Scoping Review methodology was used. Three research questions aim to identify how Life Skills are defined in the field of health promotion at school, to see whether a conceptual and consensual definition exists, and, if relevant, to propose a conceptual definition. The search was conducted in 5 databases by 3 reviewers. This study focused on full-text publications in English or French, human studies, health promotion in school, school pupils, teacher training, and with a definition of Life Skills. Publications on after-school activities, higher education outside teacher training, adult education, other than peer-reviewed scientific papers were excluded.Results: 48 publications were included in English and 7 in French. NVIVO was used to determine and compare the French and English terms used for Life Skills and their definitions. According to the three research questions, (i) the terms used to define Life Skills are diverse and numerous, with different purposes at school in relation to health promotion, and different taxonomies, and relate to different areas of research; (ii) no consensual, conceptual definition of Life Skills was found; (iii) further semantic, epistemological and ontological clarifications are required.Conclusion: Some conceptual definitions of Life Skills exist without consensus. Life Skills being at the crossroads between different fields could explain this and is illustrated by the multiplicity and diversity of the terms employed, and the various taxonomies and purposes used at school in health promotion. This may also explain why they are difficult to evaluate. Defining Life Skills consensually cannot be achieved due to the diversity of research perspectives from different fields.